2019
DOI: 10.3389/fphys.2019.01420
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Baroreflex Function in an Ovine Model of Chronic Heart Failure Induced by Multiple Coronary Microembolizations

Abstract: Testing new therapies in heart failure (HF) requires a chronic stable model of HF in large animals. Microembolization of the coronary arteries has been used to model HF previously; however, neural control has not been previously explored in this model. Thus the aim of this study was to further characterize neural control in this model of HF. HF was induced by infusion of microspheres (45 micron; 1.3 ml) into the proximal left coronary artery or left descending coronary arteries, with three sequential embolizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…To induce HF, animals had microspheres infused into their coronary arteries as described previously (Abukar et al, 2019). Briefly, sheep were fasted for 24 h prior to surgery and anesthesia was induced with intravenous propofol (5 mg/kg, i.v.…”
Section: Heart Failure Inductionmentioning
confidence: 99%
“…To induce HF, animals had microspheres infused into their coronary arteries as described previously (Abukar et al, 2019). Briefly, sheep were fasted for 24 h prior to surgery and anesthesia was induced with intravenous propofol (5 mg/kg, i.v.…”
Section: Heart Failure Inductionmentioning
confidence: 99%
“…We have previously shown that this model of heart failure has a higher resting heart rate than equivalent healthy controls [ 4 ]. This is consistent with the well-established activation of the renin-angiotensin system and the sympathetic nervous system in heart failure [ 5 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anaesthesia depth was monitored throughout the surgery by an absence of the corneal reflex and an absence of a withdrawal response to a noxious pinch. The left or right femoral artery was accessed percutaneously using an 8F (CORDIS®, USA) sheath and under fluoroscopic guidance, the left main coronary artery was then cannulated, and the catheter advanced into either the proximal left main coronary artery or left descending coronary arteries as described before [ 4 ]. To induce heart failure with reduced ejection fraction sheep underwent sequential weekly (1–3 weeks) embolizations using polystyrene latex microspheres (45 μm; 1.2 mL, approximately 650 microspheres, Polysciences, Warrington, PA, USA).…”
Section: Methodsmentioning
confidence: 99%